ответ: (3y + 1)(y - 1)
Пошаговое объяснение:
ax² + bx + c = a(x - x₁)(x - x₂)
Ищем корни :
3y² - 2y - 1 = 0
D = 4 + 12 = 16
y₁ =
y₂ =
Подставляем найденные корни в ту самую формулу:
3y² - 2y - 1 = 3(y - (-1/3) )(y - 1) = (3y + 1)(y - 1)
ответ: (3y + 1)(y - 1)
Пошаговое объяснение:
ax² + bx + c = a(x - x₁)(x - x₂)
Ищем корни :
3y² - 2y - 1 = 0
D = 4 + 12 = 16
y₁ =![\frac{-(-2) - \sqrt{16} }{2*3} = -\frac{2}{6} = -\frac{1}{3}](/tpl/images/1794/9369/0530f.png)
y₂ =![\frac{-(-2) +\sqrt{16} }{2*3} = \frac{6}{6} =1](/tpl/images/1794/9369/4a790.png)
Подставляем найденные корни в ту самую формулу:
3y² - 2y - 1 = 3(y - (-1/3) )(y - 1) = (3y + 1)(y - 1)